Finite Element Model Updating of Natural Fibre Reinforced Composite Structure in Structural Dynamics - M. S. M., Sani; N. A. Z., Abdullah; Siti Norazila, Zahari; Siregar, J. P.; M. M., Rahman (EDP Sciences, 2016)
Model updating is a process of making adjustment of certain parameters of finite element model in order to reduce discrepancy between analytical predictions of finite element (FE) and experimental results. Finite element model updating is considered as an important field of study as practical application of finite element method often shows discrepancy to the test result. The aim of this research is to perform model updating procedure on a composite structure as well as trying improving the presumed geometrical and material properties of tested composite structure in finite element prediction. The composite structure concerned in this study is a plate of reinforced kenaf fiber with epoxy. Modal properties (natural frequency, mode shapes, and damping ratio) of the kenaf fiber structure will be determined using both experimental modal analysis (EMA) and finite element analysis (FEA). In EMA, modal testing will be carried out using impact hammer test while normal mode analysis using FEA will be carried out using MSC. Nastran/Patran software. Correlation of the data will be carried out before optimizing the data from FEA. Several parameters will be considered and selected for the model updating procedure.